Asesmen Psikologis Berdasarkan Nilai Kemanusiaan : Refleksi Etika dalam Bimbingan dan Konseling - Juliet Resa Armelimentara Tsu (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Psychological assessment is an important part of the guidance anc counseling process, because it provides a comprehensive picture of the condition, potencial, and needs of the client. However, behind the assessment process that apperars scientific and systematic, there is an ethical responsibility that cannot be ignored andforgotten in it’s handling, especially in maintaining the confidentiality of information and the client’s identity and ensuring that the assessment is fair and objective. In this discussion, there are two crucisl issues that are often overlooked by counselors in a daily basis, namely how to maintain the client’s trust through the protection of assessment information data, and how to avoid bias or judgment influenced by subjective factors. Through a literature study, this discussion is expected to be able to emphasizw the importance of emplementing basic principles of professsional ethics, such as informed consent, transparency of the assessment process, and restrictions on access to result that can only be approved bt authorized parties. On the other hand, this discussion also raises the challenges faced by counselors, and there are several solution approaches offered to help counselor perfomance. With a more humane approach, this discussion invites counselors not only to become reliable users of test tools, but also guardians of humanitarian values in every assessment process carried out.